Quantifying production rates and size fractions of parrotfish‐derived sediment: A key functional role on Maldivian coral reefs. Issue 22 (3rd November 2021) - Yarlett, Robert T.; Perry, Chris T.; Wilson, Rod W.
Abstract: Coral reef fish perform numerous important functional roles on coral reefs. Of these, carbonate sediment production, as a by‐product of parrotfish feeding, is especially important for contributing to reef framework construction and reef‐associated landform development. However, only limited data exist on: (i) how production rates vary among reef habitats as a function of parrotfish assemblages, (ii) the relative importance of sediment produced from eroded, reworked, and endogenous sources, or (iii) the size fractions of sediment generated by different parrotfish species and size classes. These parameters influence not only overall reef‐derived sediment supply, but also influence the transport potential and depositional fate of this sedimentary material. Here, we show that parrotfish sediment production varies significantly between reef‐platform habitats on an atoll‐margin Maldivian reef. Highest rates of production (over 0.8 kg m −2  year −1 ) were calculated in three of the eight platform habitats; a rubble‐dominated zone, an Acropora spp. dominated zone, and a patch reef zone. Habitat spatial extent and differences in associated parrotfish assemblages strongly influenced the total quantities of sediment generated within each habitat. Nearly half of total parrotfish sediment production occurred in the rubble habitat, which comprised only 8% of the total platform area. Over 90% of this sedimentary material originated from eroded reef framework as opposed to being reworked existing or endogenously produced sediment, and comprised predominantly coral sands (predominantly 125–1000 µm in diameter). This is comparable to the dominant sand types and size fractions found on Maldivian reef islands. By contrast, nearly half of the sediment egested by parrotfish in the Acropora spp. dominated and patch reef habitats resulted from reworked existing sediments. These differences between habitats are a result of the different parrotfish assemblages supported. Endogenous carbonate production was found to be insignificant compared to the quantity of eroded and reworked material. Our findings have important implications for identifying key habitats and species which act as major sources of sediment for reef‐island systems. Abstract : Our findings show that parrotfish sediment production varies between reef habitat types as a function of the species assemblages and fish sizes supported. The origins of this material (i.e., bioerosion of reef substrate, sediment reworking, or endogenous production) also varies between habitat types because of the species and sizes of parrotfish present. In addition, we show that all species studied produce sediment size fractions suitable for shoreline maintenance.